The role of Brazilian public banks facing inequality - Adriana Nunes Ferreira; Ana Rosa Ribeiro de Mendonça; Simone Silva de Deos (International Labour Organization (ILO), 2016)
In capitalist economies, money is a strategic asset as liquidity is desirable since the future is unknown and uncertainty exists. In these economies, banks are key agents, being creators of endogenous money. And like all capitalist agents, banks make decisions in pursuit of capital valorization and have liquidity preference. At the same time, they play an important role in financing fundamental spending decisions, which contribute to income and employment creation, and are crucial to promote economic and social development. Their supply of credit, which rests on the banks' decisions of capital application that, take into account their liquidity preference, would not necessarily be balanced among different activities, agents, sectors and regions. In order to face this, it is necessary to rely on count on institutions and policies that go against the typical market behavior. Brazilian banking system is marked by the presence of large domestic banks, both private and public. At the end of 2012, the Brazilian public bank system was responsible for 43.8% of the country's banking system assets. Among them the Brazilian Development Bank, the Banco do Brasil and the Caixa, This paper discussed some measures of the public financing system that affect inequality - even when they do not have the purpose of facing inequality as a mandate. The first one discussed is the countercyclical measures of BNDES, as the main provider of long-term financing investment and its estimated impact on employment generation. The second program is 'Minha Casa Minha Vida' (MCMV), which intends to face the low income families housing deficit and also has an important countercyclical purpose. This program has been carried out by Caixa. The third and final, focuses on the use of the Constitutional Funds by the federal regional banks (BASA and BNB) and Banco do Brasil (BB) in measures that deal directly with regional inequalities. The hypothesis of this paper was: since 2003, a development policy for the country began to be designed, although timidly and with too many constraints. In this perspective, the role performed by public banks expresses one dimension of the development policy undertaken by the Brazilian Government. With that purpose, the paper was organized as follows: after this introductory section, a short presentation of the history of the most important Brazilian federal banks was made (second section). The three experiences were the subject of the third section. The last section brings together our final comments.
Keywords: 330